Using Crossword Puzzle to Increase Students’ Vocabulary Mastery in Junior High School - Surtiyem Surtiyem; Lusi Nurhayati; Yuyun Yulia (CV. Media Digital Publikasi Indonesia, 2026)
This study aims to improve students’ vocabulary mastery through the use of crossword puzzles in a classroom action research setting conducted in two cycles. The participants were 25 seventh-grade students at SMP Negeri 2 Karau Kuala, whose initial vocabulary proficiency was identified as low based on the pre-test, with the majority scoring within the fair and poor categories. The intervention involved implementing crossword puzzles as a learning medium designed to enhance students’ engagement, motivation, and retention of vocabulary through active learning strategies. Data were collected through pre-tests, formative tests, post-tests, questionnaires, observations, and field notes. The results of Cycle 1 showed a moderate improvement, with students beginning to demonstrate higher levels of participation and vocabulary recall, although some still struggled with understanding instructions. After revising the lesson plan and improving instructional clarity in Cycle 2, students’ vocabulary mastery increased significantly, as evidenced by the rise in students who achieved ratings of 3 and 4 and the absence of students in the lowest category. Qualitative findings also revealed enhanced confidence, reduced learning anxiety, and more collaborative classroom interactions during the learning process. Overall, the study concludes that crossword puzzles are an effective and engaging medium for improving vocabulary mastery among junior high school students. These findings suggest the need for further exploration of digital crossword tools, long-term retention effects, and the application of similar strategies to other language competencies.